Diversidade e estruturação genética do golfinho-pintado-pantropical (Stenella attenuata) no Sudoeste e Norte do Oceano Atlântico e no Oceano Pacífico’ - Teixeira, Fernanda Lopes (2021)
Pantropical-spotted-dolphin, Stenella attenuata (Gray 1846) occurs in temperate and tropical waters of the Atlantic, Pacific and Indian oceans. To evaluate the genetic diversity and population structure of the species on the Brazilian coast and to compare these results with those obtained for other locations, 28 specimens were sequenced for the mitochondrial DNA control region and 125 GenBank haplotypes were added in the analyzes from five locations the Eastern Tropical Pacific (92), four locations the Hawaii (12), Solomon Islands (14) and the North Atlantic Ocean (7). In addition, ten microsatellite loci were evaluated for 20 specimens from the Santos Basin in Brazil. In the Brazilian coast, nine haplotypes were found, high values of haplotypic diversity (Northeast: 0.93 +/- 0.12; South / Southeast: 0.70 +/- 0.06) and from moderate to low nucleotide diversity (Northeast: 0.027 +/- 0.02; South / Southeast: 0.007 +/- 0.00). For microsatellite loci, the observed heterozygosity values ranged from 0.450 to 0.950 and expected heterozygosity from 0.619 to 0.942. It was evidenced that the pantropical-spotted-dolphins of the Southwest Atlantic Ocean have high levels of genetic diversity and that in this region there are at least two distinct populations, with differentiation between the other ocean basins evaluated. This study presents the first genetic data for the species in the South Atlantic. The continuity of this study is important so that the area of distribution can be better represented.